حفظ العلاقة بين حفظ القرآن ودافعية تعلم اللغة العربية لدى الطالبات في الصف الثالث المتوسط بمعهد تحفيظ القرآن مؤسسة Islamic Centre ميدان سومطرة الشمالية - Azzahrah, Yamila (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
Research to see a relationship between memorizing the Qur’an and the motivation to learn the Arabic language among female students in the third intermediate grade at the Qur’an Memorization Institute, Islamic Center Foundation, North Sumatra Square. Its purpose is to know the relationship between memorizing the Qur’an and the motivation to learn the Arabic language among female students in the third intermediate grade at the Qur’an Memorization Institute, Islamic Center Foundation, North Sumatra Square. The method used is the quantitative method of the relational type and the method of analyzing the data used is the statistical method. The result of this research is that there is no relationship between memorizing the Qur’an and the motivation to learn the Arabic language among female students in the third intermediate grade at the Qur’an Memorization Institute, Islamic Center Foundation, Medan, North Sumatra, and the value of the correlation coefficient is 0.274 for the first section and 0.251 for the second section. The alternative hypothesis (Ha) is rejected and the null hypothesis is accepted (Ho).